Children's perspectives on neighbourhood barriers and enablers to active school travel: A participatory mapping study - Wilson, Katherine; Coen, Stephanie E.; Piaskoski, Angela; Gilliland, Jason A. (The Canadian geographer, 2019)
Children today are spending more sedentary time indoors than time playing and being active outdoors. The daily journey to and from school represents a valuable opportunity for children to be physically active through active school travel. The majority of research on children's active school travel omits children from the research process even though children interpret their environments in fundamentally different ways than adults. Our research uses innovative participatory mapping and qualitative GIS methods to examine how children's perceptions of their environments influence their school journey experiences. Through our thematic analysis of 25 map‐based focus groups, we identified three main themes characterizing barriers and enablers to active school travel: safety‐related, material, and affective features. By positioning children as experts of their environments in our participatory methodology, our findings provide an important counterpoint to the adultist privilege characterizing the majority of research on children's active school travel. Environmental features that mattered for children's school journeys took on multiple meanings in their eyes, demonstrating that children's perspectives must be engaged to inform interventions to promote active school travel. We thus argue that identifying barriers and enablers to active school travel for children requires engaging children's views. Points de vue des enfants sur les obstacles et les facilitateurs du quartier pour un transport scolaire actif : une étude de cartographie participative Les enfants passent aujourd'hui plus de temps à faire des activités sédentaires à l'intérieur qu'à jouer et à être actifs à l'extérieur. Les déplacements quotidiens aller‐retour à l'école constituent une occasion idéale pour que les enfants soient physiquement actifs par le truchement du transport scolaire. La majorité des recherches sur le transport scolaire actif des enfants omettent les enfants dans le processus de recherche même si les enfants interprètent leurs environnements de manières fondamentalement différentes des adultes. Notre recherche utilise des méthodes innovatrices de cartographie participative et de SIG qualitatif pour examiner la façon dont les perceptions qu'ont les enfants de leurs environnements influencent leurs expériences de leurs trajets scolaires. Au moyen de notre analyse thématique de 25 groupes de discussion, nous avons recensé trois thèmes principaux caractérisant les obstacles et les facilitateurs d'un transport scolaire actif : les caractéristiques affectives, matérielles et reliées à la sécurité. En positionnant les enfants comme des experts de leurs environnements dans notre méthodologie participative, nos conclusions fournissent un contrepoint important aux privilèges des adultes caractérisant la majorité des recherches sur le transport scolaire actif des enfants. Les caractéristiques environnementales qui importaient pour les trajets scolaires des enfants ont pris plusieurs significations à leurs yeux, démontrant que les points de vue des enfants doivent être retenus afin de faire des interventions éclairées pour promouvoir un transport scolaire actif. Nous soutenons donc que l'identification des obstacles et des facilitateurs du transport scolaire actif des enfants nécessite que l'on retienne les points de vue des enfants. Key Messages Children have meaningful insight to offer towards a better understanding of how their local environment influences active school travel behaviours. The use of participatory mapping and qualitative GIS methodology provides a unique opportunity for children to share their spatial knowledge. Furthering our understanding of how children's perceptions influence their journey to and from school will help to inform policy and practice supporting localized active school travel interventions.